The Negative Impact of Posttraumatic Stress Disorder on Working Memory of Icelandic University Students - Hekla Diljá Hlynsdóttir 1994- (2018)
Working memory is a complex cognitive system essential for everyday living. It is important for all kinds of cognitively demanding activities such as reading, writing and carrying out conversations. Working memory capacity has been compared to a resource that ,,feeds'' working memory. Is the ability to keep information active in working memory while at the same time inhibit irrelevant information. Individuals with higher working memory capacity get less disturbed by previously learned information while performing cognitive tasks and they are better at managing their attention and get less distracted by environmental stimulus. Recent studies revealed that individuals with experience of trauma and PTSD diagnosis have memory impairment and lack concentration in regular life situations, indicating impairment in working memory. The present study measured working memory and symptoms of PTSD among Icelandic university students at Reykjavík University. As expected, participants with PTSD showed significantly worse performance on OSPAN and Backward Digit Span than participants without PTSD. Participants with PTSD performed worse on immediate and delayed recall than participants without PTSD. Participants with PTSD performed better on Forward Digit Span than participants without PTSD. Vinnsluminni er flókið hugrænt kerfi sem nauðsynlegt er fyrir athafnir í daglegu lífi eins og til dæmis við lestur, skrift og að halda uppi samræðum. Vinnsluminnisspönn hefur verið líkt við afl sem nokkurn veginn skammtar vinnsluminni upplýsingum. Einstaklingar með háa vinnsluminnisspönn truflast síður af áður lærðum upplýsingum og umhverfisáreitum meðan á hugrænu verkefni stendur og þeir eru betri í að halda og stjórna athygli sinni. Nýlegar rannsóknir hafa sýnt að einstaklingar sem hafa lent í áföllum hafa lélegt minni og skortir einbeitingu, sem bendir til skaða í vinnsluminni. Þessi tiltekna rannsókn mælir vinnsluminni með tveimur hefðbundnum vinnsluminnisprófum og einu óhefðbundnu prófi og einkenni áfallastreituröskunar hjá íslenskum ...